Analisis Sikap Masyarakat terhadap Aplikasi Traveloka untuk Pemesanan Tiket Pesawat Online Kota Pontianak - Mira Wulandari (Departement of Mathematics Education, 2022)
Traveloka is one of the services engaged in booking flight tickets to make it easier for people who want to travel. Traveloka is a ticketing service site in the form of e-ticketing or electronic tickets without the need to book manually or using paper. This study aims to determine the use of online ordering application technology in the people of Pontianak city. The problem that arises is not understanding the use or booking of tickets online for the Traveloka application. To answer the existing ones, scientific research using the TAM testing method is needed which is considered suitable for testing problems, as well as to test empirical evidence about the use of the Traveloka application to users. The results of this study state that Variable perceived usefulness affects variable attitude toward using, because the value is equally good and has a negative relationship and so it has no significant effect. The perceived ease of use of variables affects the attitude toward using variables because the values are equally good and have a positive relationship and thus have a significant effect. The variables perceived usefulness and perceived ease of use affect the attitude toward using variables because they are equally good and have a positive relationship so they have a significant impact.